ANALISIS STRATEGI KOMUNIKASI DALAM IMPLEMENTASI KEBIJAKAN ASI EKSKLUSIF DAN TINGKAT PENGETAHUAN IBU DI PUSKESMAS ALALAK TENGAH KOTA BANJARMASIN - Laila Qadariah (Jurnal Mutakallimin : Jurnal Ilmu Komunikasi, 2018)
The basic capital of quality human formation begins since the baby is in the content is accompanied by the provision of breast milk (breast milk) from an early age, especially Exclusive breastfeeding is giving only breast milk to infants from birth until 6 months old. The 1990 Convention on the Rights of the Child, among others confirms that optimal growth is one of the rights child. Means breast milk in addition is a necessity, is also a baby's rights which must be fulfilled by his parents. It has been popularized in the week ASI World 2000 with Theme: "Breastfeeding is a mother's right; Breastfeeding is a baby right "(DEPKES  RI, 2011)Approach method used in this research use mixed methods are qualitative and quantitative with sequential model with form sequential explanatory design (Cresswell, 2009, in Sugiyono, 2012: 409). To answer the formulation of the first and third problems use qualitative normative approach, while to answer the problem formulation secondly using a quantitative approach.